Dynamic Stability Improvement of Multimachine Power Systems using ANFIS-based Power System Stabilizer - Agung Budi Muljono; I Made Ginarsa; I Made Ari Nrartha (Universitas Ahmad Dahlan, 2015)
Modern power system are very vurnerable to against load fluctuation during their operation. Load fluctuation identified as small disturbance is important to test dynamic (small signal) stability. This research is focused on improvement of multimachine dynamic stability by using ANFIS-based power system stabilizer (proposed PSS). ANFIS method is proposed because the ANFIS computation is more efective than Mamdani fuzzy computation. Simulation results show that the proposed PSS is able to maintain the dynamic stability by decreasing peak overshoot (Po) to the value -3,37´10-5 pu/pu and accelerating settling time (St) to the time 4.01 s for rotor speed deviation Machine-2. Also, the Po is decreased to the value -3,37´10-5 pu/pu and the St is accelerated to the time 3.98 s for rotor speed deviation Machine-3.